Passive immunotherapy targeting amyloid-β reduces cerebral amyloid angiopathy and improves vascular reactivity. (22nd October 2015) - Bales, Kelly R.; O'Neill, Sharon M.; Pozdnyakov, Nikolay; Pan, Feng; Caouette, David; Pi, YeQing; Wood, Kathleen M.; Volfson, Dmitri; Cirrito, John R.; Han, Byung-Hee; Johnson, Andrew W.; Zipfel, Gregory J.; et al.
Abstract : Cerebral amyloid angiopathy is characterized by accumulation of β-amyloid in the walls of leptomeningeal and cortical arterioles and is thought to contribute to stroke and dementia. Bales et al. report that passive immunotherapy targeting β-amyloid reduces angiopathy and improve vascular reactivity in transgenic mouse models. Abstract : Abstract : Prominent cerebral amyloid angiopathy is often observed in the brains of elderly individuals and is almost universally found in patients with Alzheimer's disease. Cerebral amyloid angiopathy is characterized by accumulation of the shorter amyloid-β isoform(s) (predominantly amyloid-β40 ) in the walls of leptomeningeal and cortical arterioles and is likely a contributory factor to vascular dysfunction leading to stroke and dementia in the elderly. We used transgenic mice with prominent cerebral amyloid angiopathy to investigate the ability of ponezumab, an anti-amyloid-β40 selective antibody, to attenuate amyloid-β accrual in cerebral vessels and to acutely restore vascular reactivity. Chronic administration of ponezumab to transgenic mice led to a significant reduction in amyloid and amyloid-β accumulation both in leptomeningeal and brain vessels when measured by intravital multiphoton imaging and immunohistochemistry. By enriching for cerebral vascular elements, we also measured a significant reduction in the levels of soluble amyloid-β biochemically. We hypothesized that the reduction in vascular amyloid-β40 after ponezumab administration may reflect the ability of ponezumab to mobilize an interstitial fluid pool of amyloid-β40 in brain. Acutely, ponezumab triggered a significant and transient increase in interstitial fluid amyloid-β40 levels in old plaque-bearing transgenic mice but not in young animals. We also measured a beneficial effect on vascular reactivity following acute administration of ponezumab, even in vessels where there was a severe cerebral amyloid angiopathy burden. Taken together, the beneficial effects ponezumab administration has on reducing the rate of cerebral amyloid angiopathy deposition and restoring cerebral vascular health favours a mechanism that involves rapid removal and/or neutralization of amyloid-β species that may otherwise be detrimental to normal vessel function.